1997
DOI: 10.1038/bjc.1997.74
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cancer in the elderly: discrepancies between self-reported and registry data

Abstract: Summary Data on self-reported cancer by a sample of 3349 elderly persons in the south-west of France were validated against registry data in the same region: only 21% of the persons on the cancer registry reported occurrence of cancer. Breast cancer was found to be most frequently accurately reported.Keywords: elderly; validity; questionnaire; registry recordsIn both large cohort and genetic studies, the absence of a population based cancer register for convenient identification of individuals with cancer ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 9 publications
1
9
1
Order By: Relevance
“…There are several reasons that may explain the reporting patterns observed in our study. It has been suggested that cancers with clear‐cut diagnostic criteria, such as breast cancer, are more likely to be self‐reported than cancers whose diagnostic procedures are ambiguous 14,15 . For example, an elevated prostate surface antigen (PSA) does not give a clear‐cut diagnosis of prostate cancer, which may be confusing to patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reasons that may explain the reporting patterns observed in our study. It has been suggested that cancers with clear‐cut diagnostic criteria, such as breast cancer, are more likely to be self‐reported than cancers whose diagnostic procedures are ambiguous 14,15 . For example, an elevated prostate surface antigen (PSA) does not give a clear‐cut diagnosis of prostate cancer, which may be confusing to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Further, advancing age at the time of questionnaire completion was positively associated with false negative and false positive reporting in our study. Previous studies 14,15 reported that the main reason for false negative and false positive reporting among older persons was declining cognitive functioning. For some, cancer may also be perceived as a ‘taboo’ subject that is associated with fear and stigma, thus making it difficult for doctors to acknowledge and discuss their diagnosis 22 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, sensitivities ranged from 15.5% to 90.0% for self-reported prostate cancer, and from 36.9% to 85.3% for self-reported melanoma. [5][6][7][8] However, the findings from these studies may not be generalizable to other populations, possibly including FDNY firefighters and emergency medical service (EMS) workers, given the recent focus on World Trade Center (WTC)-related illnesses, including cancer.…”
mentioning
confidence: 99%
“…However, this method of cancer ascertainment may introduce inaccuracies, because of under-or over-reporting by patients or proxies [1][2][3]. For example, errors in self-report may arise from lack of knowledge of tumour type, or because pre-malignant lesions may be confused with actual cancers, such as in cervical disease and skin lesions [2].…”
Section: Introductionmentioning
confidence: 96%